2021
DOI: 10.3389/fmicb.2021.645070
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Composition and Diversity in Four Ophiuroid Species: Divergence Between Suspension Feeder and Scavenger and Their Symbiotic Microbes

Abstract: Gut microbiota have important roles in the survival and adaptation of the host. Ophiuroids, as the worldwide dominant benthos, have ecological roles in benthic–pelagic coupling in the sea floor. However, little is known about the composition and diversity of their gut microbiota and its potential functions in benthic ecosystems. In present study, we preformed 16S rRNA sequencing and function analysis in four dominant species (Stegophiura sladeni, Ophiopholis mirabilis, Ophiura sarsii vadicola, and Ophiura kinb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In this study, the significantly accumulated Zn concentration in the intestine illustrated that 60 mg Zn kg −1 of dietary nZnO released more Zn than ZnSO 4 in the fish body, thus providing the physiological functions in fish. 15,23 The core microorganisms identified in our study were the same species commonly found in other fish, [27][28][29] but there were differences in species abundance. The most abundant microorganisms (Photobacterium and Mycoplasma) colonized in the 60 mg Zn kg −1 ZnSO 4 exposure group carried out the metabolic activities of nutrients (glucose, lipid and protein) through the reductive citrate cycle (Arnon-Buchanan cycle) pathway, and then efficiently produced ATP through oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, the significantly accumulated Zn concentration in the intestine illustrated that 60 mg Zn kg −1 of dietary nZnO released more Zn than ZnSO 4 in the fish body, thus providing the physiological functions in fish. 15,23 The core microorganisms identified in our study were the same species commonly found in other fish, [27][28][29] but there were differences in species abundance. The most abundant microorganisms (Photobacterium and Mycoplasma) colonized in the 60 mg Zn kg −1 ZnSO 4 exposure group carried out the metabolic activities of nutrients (glucose, lipid and protein) through the reductive citrate cycle (Arnon-Buchanan cycle) pathway, and then efficiently produced ATP through oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 59%
“…The sequences were clustered into three clades. Both Clade I and Clade II contained reference sequences from Dong et al ( 28 ). Clade I was mainly a group of O. sarsii in Funka Bay and O. sarsii vadicola in the Yellow Sea (SJP and SSYS).…”
Section: Resultsmentioning
confidence: 99%
“…Clade I was the aggregation of groups SBL and SSYS. Clade II contained a variety of sequences, including those ASVs from groups SBL and SSYS, shared ASV sequences, and reference sequences from Dong et al ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ZR0006, a Firmicutes (12.4% in spiny lobster, 0.6% in European lobster) differentiates the gut microbiota of two lobster species. Candidatus are novel lineages of Mollicutes, abundant only in the gut of crustaceans [ 18 , 20 , [71] , [72] , [73] ] and other invertebrate species [ 74 , 75 ] while very rare in vertebrate animals. As a core gut microbiota, they play a positive role in the health and immunity of marron, a freshwater crayfish species native to Western Australia [ 18 , 76 ].…”
Section: Discussionmentioning
confidence: 99%